Physical Characterization of a Deep Weathering Profile Over Rhyolite in Humid Tropical Peninsular Malaysia - Raj, John Kuna (Springer Verlag, 2018)
The weathering profile, exposed at 38.2 km of the Kuala Lumpur—Karak Highway, can be differentiated into three broad zones; the topmost Zone I (pedological soil) comprising A, B and C soil horizons and made up of clayey silty sand with indistinct relict bedrock textures. The intermediate Zone II (saprock) consists of gravelly silty sand with distinct relict bedrock texture and structures, and can be sub-divided based on differences in volumes of litho-relicts. The bottom Zone III (bedrock) is a continuous outcrop of rhyolite with alteration along discontinuity planes; its upper surface marked by an unconfined groundwater table. The weathering zones thin towards valley sides and can be assigned rock mass weathering grades; Zones I and II defining the residual soil over bedrock. Constant volume samples in Zone II show an upward decrease in dry unit weights, porosities and silt contents, but a corresponding increase in clay contents. Constant volume samples in Zone I show it to be distinct from Zone II with large clay contents but low porosities and silt contents. Decreasing fine clay contents with depth and stained quartz grains show pedological processes to have given rise to Zone I. As the silt-sized (sericite) particles mainly originate from alteration of bedrock feldspars and later break-down to clay-sized (illite and kaolinite) particles, a textural weathering index (Iw) based on the ratio of clay to silt and clay contents, is proposed to describe the progress of weathering within the profile. It is concluded that the saprock results from in situ alteration of the rhyolite rock mass due to lowering of an unconfined groundwater table whilst the A, B and C soil horizons have formed by pedological processes acting on saprock.